2023
DOI: 10.1111/wej.12847
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic degradation of bisphenol A by green synthesized CuO decorated nickel hexacyanoferrate nanocomposite

Abstract: Bisphenol A (BPA), a chemical additive in polycarbonate plastics and epoxy resins, is suspected to be an endocrine‐disrupter. Extensive use and irregular treating methods have led to frequent detection of BPA in wastewater, raising demand for their removal by efficient nanomaterials‐based technique. Nanocomposite CuO@NiHCF was synthesized via green method using Citrus aurantium peel extract. Crystalline structure (particle size <50 nm) of CuO@NiHCF was analysed by microscopic and spectroscopic analysis. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…Similar results were also reported in the literature for the compounds CuO-NiHCF, Mn-CuO, ZnS-ZnO and Ag-ZnO. 39,[41][42][43]…”
Section: Optical Properties and Stability Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were also reported in the literature for the compounds CuO-NiHCF, Mn-CuO, ZnS-ZnO and Ag-ZnO. 39,[41][42][43]…”
Section: Optical Properties and Stability Analysissupporting
confidence: 90%
“…Environmental water reservoirs consist of naturally organic materials, such as humic acid (HA), with quantities ranging from 0.1 to 20 mg L −1 . 27,42 It has been discovered that HA interacts with water treatment procedures to variable degrees; therefore, it is interesting to study the probable impact of HA on ANT breakdown by Cu@ZnO. The ANT degradation experiment used (2 mL; 0.1 and 1 M) HA to test the influence on the degradation of 10 mgL −1 ANT by Cu@ZnO.…”
Section: Optimization Factor For Photocatalytic Degradation Of Ant An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Through literature surveys, it was observed that Ag doped nanocomposites such as Ag@ZnONSt, 19 Ag/LaTiO 3, 20 CuO/TiO 2 /PANI, 21 Ag‐CuS, 22 Ag/ZnO, 23 and graphene/Ag‐doped TiO 2 24 are synthesized for the removal of selected pesticides shown Table 2. Because of environmental concerns and the implication of green chemistry, there is the trend for the synthesis of doped nanoparticles using plant feedstock (plants, roots, flowers, leaves) which contain several types of phytochemicals such as polyphenols, cellulose, saponins, sugars, flavonoids, and amino acids 25–31 . Therefore, it was envisioned to synthesize silver‐doped metal hexacyanoferrates (Ag@MHCFs) via the green route.…”
Section: Introductionmentioning
confidence: 99%
“…Because of environmental concerns and the implication of green chemistry, there is the trend for the synthesis of doped nanoparticles using plant feedstock (plants, roots, flowers, leaves) which contain several types of phytochemicals such as polyphenols, cellulose, saponins, sugars, flavonoids, and amino acids. [25][26][27][28][29][30][31] Therefore, it was envisioned to synthesize silver-doped metal hexacyanoferrates (Ag@MHCFs) via the green route. Numerous publications indicated that MHCFs complexes have superior adsorption and catalytic properties because of their inherent features, including electrochemical and spectral properties.…”
mentioning
confidence: 99%